2009
DOI: 10.1111/j.1540-8175.2009.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Live/Real Time Three‐Dimensional Transesophageal Echocardiography in the Assessment of Valvular Vegetations

Abstract: We studied 13 patients with valvular vegetations who underwent intraoperative live/real time three-dimensional transesophageal echocardiography (3DTEE) and real time two-dimensional transesophageal echocardiography (2DTEE). The 3DTEE provided incremental value on top of 2DTEE in its ability to accurately identify and localize vegetations and in identifying complications of infective endocarditis such as abscesses, perforations, and ruptured chordae. By using 3DTEE, we were able to measure vegetation volumes, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 24 publications
1
51
0
2
Order By: Relevance
“…Therefore, the study findings are of clinical relevance and add to previous studies in general populations and 5 isolated case reports of Libman-Sacks endocarditis on the complementary value of 3D-TEE to 2D-TTE or 2D-TEE for the detection, characterization, and differentiation of non-infective and infective vegetations, valve tumors, thrombus, and nodular calcifications (1316,2328,). Also, 3D-TEE may have additive complementary value to 2D-TEE in the diagnosis of embolic cerebrovascular disease in SLE.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Therefore, the study findings are of clinical relevance and add to previous studies in general populations and 5 isolated case reports of Libman-Sacks endocarditis on the complementary value of 3D-TEE to 2D-TTE or 2D-TEE for the detection, characterization, and differentiation of non-infective and infective vegetations, valve tumors, thrombus, and nodular calcifications (1316,2328,). Also, 3D-TEE may have additive complementary value to 2D-TEE in the diagnosis of embolic cerebrovascular disease in SLE.…”
Section: Discussionsupporting
confidence: 73%
“…Multiplane two-dimensional (2-D) transesophageal echocardiography (TEE) has high diagnostic value for detection of Libman-Sacks endocarditis (5,6,8,12). Three-dimensional TEE (3D-TEE) has emerged as an important complementary technique to 2D-TEE for detection and characterization of infective vegetations and valve tumors (1316). However, no previous study has been reported on the diagnostic value and clinical relevance of 3D-TEE in Libman-Sacks endocarditis.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, early investigations 64,65 of 3D TEE have demonstrated advantages over 2-dimensional TEE (which is routinely used) to better detect and delineate vegetations and to identify IE complications and their relationships with surrounding structures. Unfortunately, the lower temporal and lateral resolution with 3D echocardiography compared with 2-dimensional echocardiography leads to an overestimation of vegetation size and technically challenging visualization of fast-moving structures.…”
Section: D Echocardiography and Other Imaging Modalitiesmentioning
confidence: 99%
“…Komplementär zu den bewährten Modalitäten kann die Echtzeit-3-D-Echokardiographie ergänzen-de Hinweise zu Vegetationsgröße, Abszessausbreitung und Chordarupturen liefern [12,13]. Diese Informationen können für die Operationsplanung wichtig werden und eine Risikoabschätzung bezüglich des Auftretens von Embolien erlauben.…”
Section: Echokardiographieunclassified